3 D NiO Nanowall Hole‐Transporting Layer for the Passivation of Interfacial Contact in Inverted Perovskite Solar Cells. Issue 5 (6th February 2020) - Yin, Xin; Zhai, Jifeng; Du, Pingfan; Li, Ni; Song, Lixin; Xiong, Jie; Ko, Frank
Abstract: Nickel oxide (NiO) materials with excellent stability and favorable energy bands are desirable candidates for hole‐selective contact (HSC) of inverted perovskite solar cell (PSC). However, studies that focus on addressing interfacial issues, which are induced by the poor NiO/perovskite contact or other defects, are scarce. In this study, a facile one‐step hydrothermal strategy is demonstrated for the development of a 3 D NiO nanowall (NW) film as a promising HSC. The new NiO NWs HSC exhibits a robust and homogenous mesoporous network structure, which improved the NiO/perovskite interface contact, passivated the interfacial defect and improved the quality of the perovskite film. The optimized interface features enabled a power conversion efficiency (PCE) approaching 18 %. A diethanolamine (DEA) interlayer was introduced to further passivate the intrinsic defect of the NiO surface, resulting in better charge transfer with suppressed recombination loss. As a result, the champion PCE of the NiO NWs/DEA‐based device was increased to 19.16 % with a high open‐circuit voltage (≈1.11 V) and fill factor (>80 %), which is prominent in methylammonium lead iodide‐based inverted PSCs. Furthermore, the device exhibited better stability and lower hysteresis behavior than a conventional solution‐based NiO nanocrystal device. Abstract : Holes in the wall : The morphology of selective contact materials is critical for the charge transfer and interfacial properties of a device. A 3 D NiO nanowall has been developed as a promising passivation/active scaffold. The improved interface contact features a low defect density. The enhanced quality of the perovskite layer enables excellent efficiency and device stability.